Shine bright like a star: Hotel performance and guests' expectations based on star ratings. (October 2019) - Mohsin, Asad; Rodrigues, Helena; Brochado, Ana
Graphical abstract: Highlights: This study evaluates the service quality offered by hotels in Lisbon. The research measure specific dimensions for guests staying in 3, 4, 5 star hotels. The measurement of service gaps provided significant conclusions for management. The study extends the research on service quality applying the IPA theory. The study adds a new insights based on data from an under researched EU region. Abstract: Service excellence requires continuous efforts to sustain consistency it is destroyed relatively quickly. The expanding competition in the hotel industry needs to evaluate its service quality models continually to counteract high levels of homogeneity and deal with intense demand of the hotel guests. This study is designed to accomplish a dual purpose: 1) to evaluate the service quality offered by hotels in Lisbon based on an importancE–Performance analysis (IPA) scale and, 2) to measure the importance of specific dimensions for guests staying in three, four, and five star hotels. Segmentation, as an important outcome of the IPA, is used to identify key differences for better planning and decision-making. The findings extend the research on service quality relying on IPA theory and contributes to the literature on hotel service quality by adding new insights based on data from an under researched region of the European Union.